Auditors' Representation and Retrieval of Internal Control Knowledge - Frederick, David M. (The Accounting Review, 1991)
[This article examines the characteristics of experienced and inexperienced auditors' retrieval of internal controls from memory. Because it is possible that knowledge retrieval is a function of the manner in which information is stored in memory, this study also investigates two kinds of knowledge organization: (1) a taxonomic representation, as typified by categoric checklists; and (2) a schematic representation, as typified by information flowcharts. Although the relationship between knowledge and expertise is well documented in the literature, few accounting researchers have attempted to study the memory structures of skilled individuals (Libby and Frederick 1990; Weber 1980). Thus, this work is motivated by two broad objectives: (1) to understand the nature of expertise, which will help in assessing the boundaries of auditors' abilities and performance; and, (2) to comprehend the cognitive skills of both expert and novice auditors, which will help in facilitating skill acquisition by unseasoned individuals. One hundred thirteen auditors and 97 auditing students were used to study the retrieval characteristics of the taxonomic and schematic knowledge structures and memory differences between experts and novices. Auditors freely recalled more internal controls when such controls were organized by transaction flow. Auditing students did not possess complete knowledge organizations, and the type of representation did not affect their free recall of the controls. Across a given knowledge representation, providing subjects with complete subsets of internal controls as a memory aid did adversely affect the retrieval of additional controls in the taxonomic but not the schematic organization. Within a specific class of internal controls, however, providing subjects with a portion of the controls was detrimental to the recall of the remaining controls in both types of representation. These results suggest that an auditor's retrieval of internal controls from memory depends not only on the auditor's level of experience but also on the way in which the auditor's knowledge of controls is organized.]